(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article discusses the heat generated by various methods of heating water. The formation of sediment (scale) during heating of water confirms the existence of the ionization process in water. As a result, the movement of water molecules increases. It has been established that in devices that efficiently generate thermal energy in water (a vortex heat generator, a gravity device and an EFI generator), and when heating water, it is possible to balance the values of thermal energy received in water from energy transmitted from the outside.